1995
DOI: 10.1177/096120339500400610
|View full text |Cite
|
Sign up to set email alerts
|

Role of β2-glycoprotein I in the anticardiolipin antibody affinity for phospholipid in autoimmune disease

Abstract: The binding capacity to cardiolipin and the functional affinity of affinity-purified anticardiolipin (aCL) IgG of patients with autoimmune disease have been compared with those of individuals with malaria and acquired immunodeficiency syndrome (AIDS). The binding of autoimmune IgG aCL was enhanced gradually by the incorporation of increasing amounts of beta 2-glycoprotein I (beta 2GPI) into the assay, in contrast to that of patients with infectious diseases. In addition, there were significant reductions of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Presence of goat serum, which contains β2 GPI, considered as largely homogenous to human β2 GPI and is used commonly in aPL ELISA, decreased notably the detection of aCL in malaria sera. This is consistent with inhibition of PL binding to aPL described previously during protozoal infections and presumably due to the interference of peptidic co‐factors such as β2 GPI with antigenic interactions of aCL [11,12]. Anti‐β2 GPI antibodies were found in a small number of malaria‐exposed donors, which confirms that they are usually not detected during infectious diseases, while in APLS they are considered as more specifically associated with clinical manifestations [10,30–33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Presence of goat serum, which contains β2 GPI, considered as largely homogenous to human β2 GPI and is used commonly in aPL ELISA, decreased notably the detection of aCL in malaria sera. This is consistent with inhibition of PL binding to aPL described previously during protozoal infections and presumably due to the interference of peptidic co‐factors such as β2 GPI with antigenic interactions of aCL [11,12]. Anti‐β2 GPI antibodies were found in a small number of malaria‐exposed donors, which confirms that they are usually not detected during infectious diseases, while in APLS they are considered as more specifically associated with clinical manifestations [10,30–33].…”
Section: Discussionsupporting
confidence: 89%
“…Differences in antigen recognition by aPL may play a role in clinical presentation, since epitopes recognized in autoimmune conditions differ from those characterized during infectious diseases. In the first group, antibody targets correspond primarily either to complexes associating cardiolipin (CL) and beta2 glycoprotein‐I (β2 GPI) or other serum peptide co‐factors, or epitopes present on peptide co‐factor(s) in a native or PL‐modified form [9–12]. During infectious diseases, aPL were generally found to be peptide co‐factor‐independent and directed against PL alone [6,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The design of this study [41] was different from that of our study and the results of the two studies are not comparable. In fact, before eluting the low affinity antibodies by diethanolamine, in the study by Dueymes et al [41], sera were preincubated with increasing amounts of 2-GPI. Therefore, the binding of antibodies recognizing 2-GPI of 2-GPI/CL complex was inhibited; in the step of diethanolamine incubation, the binding of another population of aCL antibodies recognizing CL alone was also inhibited.…”
Section: Discussionmentioning
confidence: 67%
“…However, the avidity of these antibodies to the respective antigen is low in HIV as compared to that found in SLE/APS and PAPS patients. In a previous study [41], the so-called 'functional affinity' of aCL antibodies in SLE and HIV patients' sera was detected; it was found that the 'functional affinity' of SLE sera was gradually decreased (after diethanolamine treatment), with increasing amounts of 2-GPI added in the fluid phase; this was not observed in aCL-positive sera from HIV-infected individuals. The design of this study [41] was different from that of our study and the results of the two studies are not comparable.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation